2017
DOI: 10.2166/wp.2017.132
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of water scarcity in a leap-forward developing arid region: a system dynamics model of Xinjiang Uygur Autonomous Region

Abstract: The leap-forward development policy emphasizes water resource scarcity. Given the importance of water resources to an economy, especially in arid areas, this paper explores various management strategies that could be used in the semi-arid region of Xinjiang to increase the effectiveness and efficiency of multifunctional water projects and support sustainable ‘leap-forward’ economic growth. Embedding the logistic growth function within a system dynamics framework, our model provides a universally implementable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…During the study period, water resources in 82.40% of Xinjiang were in deficit, and previous researches had similar conclusions. Specifically, current water resources cannot meet leap-forward development in Xinjiang (Dai et al, 2017), and water resources in Alar, a city located in southern Xinjiang, also cannot satisfy demand for economic development (Liu et al, 2019). Fortunately, WSDD in 64.65% of the region that passed the trend analysis exhibited an increasing trend, and the areas with increased WSDD were mainly distributed in northern Xinjiang, indicating that water deficit in some areas of Xinjiang has been alleviated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study period, water resources in 82.40% of Xinjiang were in deficit, and previous researches had similar conclusions. Specifically, current water resources cannot meet leap-forward development in Xinjiang (Dai et al, 2017), and water resources in Alar, a city located in southern Xinjiang, also cannot satisfy demand for economic development (Liu et al, 2019). Fortunately, WSDD in 64.65% of the region that passed the trend analysis exhibited an increasing trend, and the areas with increased WSDD were mainly distributed in northern Xinjiang, indicating that water deficit in some areas of Xinjiang has been alleviated.…”
Section: Discussionmentioning
confidence: 99%
“…As WUD irr dominated changes in the total WUD in Xinjiang in the past years, it is important to continue prompt water-saving irrigation technologies and also control the expansion of cropland areas. Reasonable planning of the cropland layout and expansion is also needed (Lei et al, 2012;Dai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Xinjiang is one of the most popular ski areas in China, holding 37 ski resorts at the end of 2017. Compared with other ski destinations in China, Xinjiang is an arid area; researchers found that climate change combined with its economic development have significantly influenced the yearly average rainfall and water resource distribution pattern (Dai, Li, & Xu, ). Climate change mitigation is a non‐negligible issue for Xinjiang.…”
Section: Methodsmentioning
confidence: 99%
“…Selecting a feedback intensity should consider whether the simulated dynamic adjustment is technically and financially feasible. In addition, it was observed that the exponential function and modified logistic function were used to describe the feedback relationship between state variables and regulatory variables [44,58]. Gain function, correlation function, and least square function were also used to dynamically modify the preset schemes [59].…”
Section: Discussionmentioning
confidence: 99%